Miles Morales : stranger tides : a Spider-Man graphic novel - Reynolds, Justin A. (Spider-Man graphic novel, 2022)
While at a launch for a brand-new video game, Spider-Man must swing into action when a villain named the Stranger, who has deemed humanity lacking, manipulates the game.